Integrating aviation and passenger rail planning (ACRP report, 2015)
"TRB's Airport Cooperative Research Program (ACRP) Report 118: Integrating Aviation and Passenger Rail Planning explores planning options, funding challenges, and potential actions to improve integration of rail services with airports, particularly in congested corridors. The report has an accompanying CD-ROM that includes an Air/Rail Diversion model. A User Guide provides direction in applying the model to evaluate different scenarios and a Technical Appendix provides supplemental information for the model." -- Publisher's description.